Riesgo conductual en el mercado de valores en Colombia entre 2010 y 2015 (2016)
In recent years, economic and finance researchers have given a prominent role to the study of economic decision-making and the role of incentive mechanisms in achieving optimal outcomes. This study uses a behavioral economic framework to identify, categorize, and analyze the conduct risk of brokers in the Colombian securities market. We evaluate brokers’ decisions to sell securities between 2010 and 2015. The empirical results indicate that approximately 80% of these decisions went beyond clients’ authorizations, involved inappropriate use of clients’ resources, failed to follow authorized advisory practices to clients, or blocked the release of information to clients.